Konsep Komsel Three Party Sebagai Implementasi Gaya Hidup Kelompok Sel Menurut Kisah Para Rasul 2:46-47 - Paulus Kunto Baskoro (Jurnal Teologi (JUTEOLOG), 2022)
Church growth is an important part of church history. One the important pillars in church growth is the cell group. The early church became a serious church in working on cell group principles as in Acts 2:46-47. The Covid-19 pandemic has made changes and shifts in the arrangement of cell groups. Before Covid 19 cell groups coulds be held in large numbers, but when the Covid 19 pandemis hit the world, cell groups could not be held in meetings with many people. The researcher is giving an explanation about the concept of cell group with the name of three party which is a simple implementation according to the principle of cell group Acts 2:46-47, especially in the present. This writing uses a descriptive literature method. The goal is that trough writing, namely : First, every believer understands the important principle in church growth through cell groups according to Acts 2:46. Second, every believer understands one of the newer models of effective cell grouping principles today. Third, every believer can implement the comsel three party concept, so that the local church experiences significant congregational growth.